Water of the world - Jankowski, Laurence; TMW Media Group (Lakewood, Colorado : Instructional Video, 2005)
This program examines the hydrologic cycle and shows the major water movement in the United States. It also examines how ground water stores and releases water and looks at lakes, major river systems in the world, and the world's estimated water supply
Title from title screen
Keywords: Water; Hydrologic cycle; Hydrology